2019
DOI: 10.1007/s11083-019-09497-0
|View full text |Cite
|
Sign up to set email alerts
|

A Discrete Duality Between Nonmonotonic Consequence Relations and Convex Geometries

Abstract: In this paper we present a duality between nonmonotonic consequence relations and well-founded convex geometries. On one side of the duality we consider nonmonotonic consequence relations satisfying the axioms of an infinitary variant of System P, which is one of the most studied axiomatic systems for nonmonotonic reasoning, conditional logic and belief revision. On the other side of the duality we consider well-founded convex geometries, which are infinite convex geometries that generalize well-founded posets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…8. There are some definitions of infinite convex geometries in the literature: see, for instance, Adaricheva (2014b), Adaricheva andNation (2016d), Jamison-Waldner (1982), Mao (2017), Mao and Liu (2012), Marti and Pinosio (2020), Wahl (2001). In view of these notions, extending the investigation of resolutions to infinite convex geometries appears to be of some interest.…”
Section: Future Work and Open Problemsmentioning
confidence: 99%
“…8. There are some definitions of infinite convex geometries in the literature: see, for instance, Adaricheva (2014b), Adaricheva andNation (2016d), Jamison-Waldner (1982), Mao (2017), Mao and Liu (2012), Marti and Pinosio (2020), Wahl (2001). In view of these notions, extending the investigation of resolutions to infinite convex geometries appears to be of some interest.…”
Section: Future Work and Open Problemsmentioning
confidence: 99%
“…It can be shown that G * is a closure operator. Moreover, for a Plott function G, the closure G * (X) is a kind of convex hull of X (for details see [10] for finite C and [13] in the general case). The inversion to the operator G * is defined by the formula:…”
Section: Closure Operatormentioning
confidence: 99%
“…8. There are some definitions of infinite convex geometries in the literature: see, for instance, Adaricheva (2014b), Adaricheva and Nation (2016), Jamison-Waldner (1982), Mao (2017), Mao and Liu (2012), Marti andPinosio (2020), Wahl (2001). In view of these notions, extending the investigation of resolutions to infinite convex geometries appears to be of some interest.…”
Section: Future Work and Open Problemsmentioning
confidence: 99%